From Democratic Backsliding to Institutional Adaptation? Constitutional Politics after Indonesia's 2024 Elections - Keisha Amalia Rahman (Indonesian Political Transformation, 2026)
Recent political developments in Indonesia have generated extensive academic debate regarding the trajectory of its democratic institutions following the 2024 General Election. Concerns surrounding judicial independence, constitutional interpretation, executive influence, and electoral governance have raised questions about whether Indonesia is experiencing democratic backsliding or institutional adaptation within an evolving constitutional order. While existing studies often frame democratic change through a dichotomy of democratic decline versus democratic resilience, this article argues that Indonesia presents a more nuanced pattern of institutional transformation. Using qualitative constitutional analysis, the study examines judicial decisions, constitutional amendments, legislative developments, parliamentary debates, and expert interviews to assess institutional change between 2019 and 2025. The findings indicate that constitutional institutions continue to demonstrate adaptive capacity despite increasing political centralization, although important concerns remain regarding checks and balances, accountability mechanisms, and institutional independence. Rather than representing irreversible democratic erosion, Indonesia illustrates a process of negotiated institutional adaptation shaped by political bargaining, legal interpretation, and evolving governance practices. The article contributes to comparative constitutional politics by proposing an analytical framework capable of distinguishing democratic adaptation from democratic backsliding in emerging democracies. The study further highlights the importance of institutional resilience, constitutional legitimacy, and civic oversight in maintaining democratic governance under conditions of political transformation. These findings provide broader theoretical insights for comparative research examining constitutional change across transitional democracies in the Global South.